ANALISIS KINERJA PEGAWAI PADA SEKRETARIAT KOMISI PEMILIHAN UMUM (KPU) KOTA PALU - Syari, Ika Widya (Katalogis, 2013)
This research aim to analyse the Officer performance of at Secretariat of General Election Commission (KPU) of Hammer Town, and know the factors of supporter and resistor of Officer performance of Secretariat of General Election Commission ( KPU) of Hammer Town. Book Study in this research that is performance, conception the PNS, Officer Ability. Research Location in Office of Secretariat of KPU of Hammer Town. Informan Election use the Purposive Sampling. By specifying 7 people as Data informan collected by through/ passing observation technique, interview, and documentation. In this research is researcher use the Theory of Performance Dessler that is Work Quality, Work Amount, needed Supervision, Attendance, Conservation. Technique analyse the data use the descriptive analysis qualitative. Pursuant to result of research menunjukan that officer performance of at Secretariat of KPU of Town Palu with the indicator 1). work quality obtained by picture that officer of Secretariat of KPU of Hammer Town with quality for pekerjaanya. This matter earn in measure of through/ passing accuration, correctness, skill and output acceptance, 2). Work amount have been reached by through/ passing volume of output and time use, 3). Supervision needed give the benefit for make-up of performance of officer of Secretariat of KPU of Hammer Town, 4). attendance Or discipline of low-civil servant at the (time) of activity of apple of morning and evening apple, however officer of Secretariat of KPU of Town of discipline Hammer in finishing work is although encumbered by the in working addition, 5). Conservation of result of observation and interview the menunjukan do not look after of better medium and this prasarana matter in resulting from repository limitation owned by Secretariat of KPU of Hammer Town. While factors becoming supporter and resistor of Officer performance of at Secretariat of General Election Commission ( KPU) of Hammer Town that is supplementary factor of institute have the character of vertical, clear regulasi, while factor of resistor of dualisme leadership, system of promotion and officer mutation.